Solution combustion synthesis of disordered spinel LiMn1.5Ni0.5O4 cathode material using PVP fuel - M. Azari; S.M. Masoudpanah; S. Alamolhoda (Electrochemistry Communications, 2025)
In this research, the LiMn1.5Ni0.5O4 powders were prepared by solution combustion method using metal nitrates as an oxidant and various amounts of polyvinylpyrrolidone (PVP) as fuel. The effects of PVP contents and calcination treatment on the Mn3+proportion, morphology, and electrochemical properties were explored. The calcination treatment included the two-step process (pretreatment at 450 °C and then calcination at 800 °C) and one-step treatment at 600 °C. Single-phase LiMn1.5Ni0.5O4 powders with disordered spinel crystal structure (space group of Fd3m) were crystallized by calcination at 600 °C at the lowest fuel contents. The LiMn1.5Ni0.5O4 particles had octahedral morphology even at the calcination temperature of 600 °C. The LiMn1.5Ni0.5O4 powders calcined using the two-step process exhibited comparable lithium-ion storage performance, including a capacity retention of 99 % following 200 charge/discharge cycles at 1C and a specific capacity of 110 mAh g−1.